And so the youth fire raged on youth and practices of democracy and empowerment in Brazil and Kenya - Kimari, Wangui (CLACSO, 2021)
Heeding the 2013 CODESRIA / CLASCO call to attend to the localized entanglements of democracy and neoliberalism, this research is oriented by the bid to see what other political spaces have been established by young people in Kenya and Brazil, and what this says about how they fit in to normative political fora with their hegemonic discourses of democracy and neoliberalism; ideologies which often seek to impose on youth particular kinds of political practices and subjectivities. Overwhelmingly, it is also an attempt to share strategies and political imaginations that have emerged from poor urban youth in both countries; approaches, I argue, that also gesture towards the futures for these youth, their urban settings, and of the ‘democratic’ and ‘neoliberal’ political processes that have been entrenched in their national spaces.